Profile of Physics E-learning Activities During The Covid-19 Pandemic: Voices from High School Students and Teachers - Iqbal Ainur Rizki; Hanandita Veda Saphira; Sefia Anggi Lestari; Ekaningtyas Wahyu Epriliyani; Nurita Apridiana Lestari; Eko Hariyono (Berkala Ilmiah Pendidikan Fisika, 2022)
E-learning is one of the trends in physics learning during the Covid-19 pandemic. However, its implementation has advantages and disadvantages that must be considered. Therefore, this study will examine the profile of e-learning physics during the pandemic from the perspective of students and teachers. The research is a mixed-method embedded design with a sample of 209 students and 9 physics teachers. Data collection techniques used were surveys and structured interviews, while data analysis techniques were carried out descriptively. The study results indicate that students tend not to find it easy to implement e-learning, with the most obstruction being network instability and the lack of internet quota. Students also do not experience an increase in learning motivation when using e-learning. Students' most frequently used platforms are Google Classroom, WhatsApp, Google Meet, and Zoom. Students rated e-learning as a whole with an average score of 6.61. Some of the teacher's responses are consistent with the student survey results. According to the teacher, planning to implement e-learning has its respective advantages and disadvantages. E-learning is one of the alternative learning activities that can be carried out during the Covid-19 pandemic or even post-pandemic, along with the increase in digitalization and information technology in the education system.